2017
DOI: 10.3389/fnins.2017.00112
|View full text |Cite
|
Sign up to set email alerts
|

Antidyskinetic Effects of MEK Inhibitor Are Associated with Multiple Neurochemical Alterations in the Striatum of Hemiparkinsonian Rats

Abstract: L-DOPA-induced dyskinesia (LID) represents one of the major problems of the long-term therapy of patients with Parkinson's disease (PD). Although, the pathophysiologic mechanisms underlying LID are not completely understood, activation of the extracellular signal regulated kinase (ERK) is recognized to play a key role. ERK is phosphorylated by mitogen-activated protein kinase kinase (MEK), and thus MEK inhibitor can prevent ERK activation. Here the effect of the MEK inhibitor PD98059 on LID and the associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 68 publications
1
21
0
Order By: Relevance
“…For example, in 6-OHDA lesioned rats, intra-striatal inhibition of PKA during L-DOPA treatment was found to attenuate both LID and its molecular correlates such as ΔFosB accumulation, p-DARPP-32 and pERK1/2 27 . Similar results have also been shown with inhibitors of ERK1/2 phosphorylation given during chronic L-DOPA treatment 28,69 . Interestingly, while these studies all found that inhibition of PKA or ERK1/2 during the L-DOPA priming period reduced LID, inhibition of ERK1/2 on the day of dyskinesia testing was not required to attenuate LID 28 .…”
Section: Discussionsupporting
confidence: 83%
“…For example, in 6-OHDA lesioned rats, intra-striatal inhibition of PKA during L-DOPA treatment was found to attenuate both LID and its molecular correlates such as ΔFosB accumulation, p-DARPP-32 and pERK1/2 27 . Similar results have also been shown with inhibitors of ERK1/2 phosphorylation given during chronic L-DOPA treatment 28,69 . Interestingly, while these studies all found that inhibition of PKA or ERK1/2 during the L-DOPA priming period reduced LID, inhibition of ERK1/2 on the day of dyskinesia testing was not required to attenuate LID 28 .…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, understanding the molecular substrates of ΔFosB and its associated activator protein-1 (AP-1) underlying altered SPN responses to DA may also help identify pharmacological targets to treat LID. In addition to previously identified genes (e.g., MAPK-related genes, Rgs16, somatostatin/G-coupled receptor genes, Nurr1, Trh) that are significantly regulated in LID models (32), AP-1mediated transcriptional changes may also lead to aberrant regulation of glutamate receptor subunits through increased expression or changes in membrane trafficking and phosphorylation states, which are known to occur after long-term DA depletion and replacement (15,35). Overall, the present data encourage developing strategies for targeting ΔFosB or its regulated genes as a therapy for LID.…”
Section: Off On Lid Off On Lid Off On Lid Off On Lid Off On Lid Off Omentioning
confidence: 99%
“…The critical point of PDE10A inhibition having synergism with D1R, but antagonism with D2R, activation cannot be construed as a global, net effect in each pathway resulting in the inhibitor anti‐LID effect. Stimulation of D1R, which increases cAMP through the olfactory type G‐protein α subunit, is associated with multiple molecular markers of LID (dopamine‐ and cAMP‐regulated phosphoprotein 32 kDa, protein phosphatase 1, mitogen‐activated protein kinase, extracellular signal‐related kinases 1 and 2, and the transcription factor, ΔFosB) . In addition, a member of the D2‐like subfamily, the D3R, that also inhibits adenylyl cyclase and suppresses cAMP, may participate in the mechanisms of LID.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of D1R, which increases cAMP through the olfactory type G-protein a subunit, 14 is associated with multiple molecular markers of LID (dopamine-and cAMP-regulated phosphoprotein 32 kDa, protein phosphatase 1, mitogen-activated protein kinase, extracellular signal-related kinases 1 and 2, and the transcription factor, DFosB). [41][42][43][44][45] In addition, a member of the D2like subfamily, the D3R, that also inhibits adenylyl cyclase and suppresses cAMP, may participate in the mechanisms of LID. Interestingly, the D3R contribution has been associated with a D1R-mediated mechanism according to a recent study in transgenic mice.…”
Section: Discussionmentioning
confidence: 99%